2023
DOI: 10.1002/ppap.202300086
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Ni/MOF‐74 catalyst packed‐bed DBD plasma for ammonia synthesis

Yang Liu,
Xiaofang Xu,
Qinlong Song
et al.

Abstract: Nonthermal plasma (NTP) provides a potential and sustainable route for the synthesis of ammonia. In this work, a Co–Ni/MOF‐74 catalyst was developed to synthesize ammonia from N2 and H2 in a dielectric barrier discharge (DBD) plasma at low temperature and atmospheric pressure. Co–Ni/MOF‐74 showed the highest ammonia synthesis rate up to 2608.70 μmol g−1 h−1 at 200°C, with V(N2):V(H2) ratio of 1:1 and specific energy input of 33.27 kJ L−1. The catalytic activity was increased by 19.57% for Co–Ni/MCM‐41 and 375%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(61 reference statements)
0
4
1
Order By: Relevance
“…It was lower than the values reported by Peng et al [46], however, they used larger gas flow rates in their work, which may have resulted in lower feedstock utilization. Patil et al [47] synthesized ammonia in a microsecond pulsed DBD plasma using a BaTiO 3 catalyst with a maximum energy efficiency of 0.34 g•kWh −1 at a specific energy input of 2.13 kJ•L −1 , which is significantly lower than the present study, mainly due to the higher specific surface area and catalytic activity of the Ni-MOF-74 catalyst than BaTiO 3 . Liu et al [48] efficiency of 0.72 g•kWh −1 , and Shah et al [34] achieved a maximum energy efficiency of 0.23 g•kWh −1 of , all of which are significantly lower than the present study.…”
Section: Comparison With Previous Workcontrasting
confidence: 69%
“…It was lower than the values reported by Peng et al [46], however, they used larger gas flow rates in their work, which may have resulted in lower feedstock utilization. Patil et al [47] synthesized ammonia in a microsecond pulsed DBD plasma using a BaTiO 3 catalyst with a maximum energy efficiency of 0.34 g•kWh −1 at a specific energy input of 2.13 kJ•L −1 , which is significantly lower than the present study, mainly due to the higher specific surface area and catalytic activity of the Ni-MOF-74 catalyst than BaTiO 3 . Liu et al [48] efficiency of 0.72 g•kWh −1 , and Shah et al [34] achieved a maximum energy efficiency of 0.23 g•kWh −1 of , all of which are significantly lower than the present study.…”
Section: Comparison With Previous Workcontrasting
confidence: 69%
“…At different discharge powers, the 5 cm electrode configuration had the highest concentration of ammonia synthesis. This indicates that this configuration’s discharge and catalytic reaction processes may have reached an appropriate matching state, ensuring the reactants’ thorough activation and reaction . The difference in performance is particularly noticeable when the discharge power is 15 W. The 5 cm electrode configuration synthesized 4755 ppm of ammonia, significantly higher than the ammonia-producing capacity of the 7 cm (3634 ppm) and 9 cm (3575 ppm) electrode configurations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This indicates that this configuration's discharge and catalytic reaction processes may have reached an appropriate matching state, ensuring the reactants' thorough activation and reaction. 27 The difference in performance is particularly noticeable when the discharge power is 15 W. The 5 cm electrode configuration synthesized 4755 ppm of ammonia, significantly higher than the ammonia-producing capacity of the 7 cm (3634 ppm) and 9 cm (3575 ppm) electrode configurations. The observed phenomenon may be attributed to reduced discharge power per unit discharge volume resulting from increased electrode length.…”
Section: Influence Of System Configuration On Ammonia Synthesis (Leng...mentioning
confidence: 96%
“…Conventional thermal catalytic ammonia synthesis commonly employs the stoichiometric N 2 /H 2 ratio (1:3), whilst under NTP conditions relevant studies showed that the N 2 -rich environment is beneficial to promote the ammonia production rate [27,39,54,57,[70][71][72]. For example, Patil et al conducted a comparative investigation of the N 2 /H 2 ratio on NH 3 formation over various metals supported on Al 2 O 3 , showing the optimal N 2 /H 2 ratio in the NTP-catalysis was either 1 or 2 depending the type of metals [27].…”
Section: N 2 -To-h 2 (N 2 /H 2 ) Ratio and Flowratementioning
confidence: 99%